Improvement of efficiency prediction for a Kaplan turbine with advanced turbulence models - Jošt, Dragica (Strojniški vestnik, 2014)
A comparison between numerical simulations and measurements of a six-blade Kaplan turbine is presented in order to determine anappropriate numerical setup for accurate and reliable simulations of Kaplan turbines. Values of discharge, torque and losses obtained bydifferent turbulence models are compared to each other and to the measurements. Steady state simulations with various turbulence modelstend to predict large errors at full discharge rate, which are the result of underestimated torque on the shaft and overestimated flow energylosses in the draft tube. The results were slightly improved with the curvature correction (CC) and Kato-Launder (KL) limiter of turbulenceproduction. Transient simulations were performed with shear-stress-transport (SST) turbulence model, the scale-adaptive-simulation (SAS) SSTmodel, and with zonal large-eddy-simulation (ZLES). Details about turbulent structures in the draft tube are illustrated in order to explain thereasons for differences in flow energy losses obtained by different turbulence models. The effects of advection schemes and mesh refinementwere tested. It was shown that all of the transient simulations considerably improved results at full discharge rate. The largest improvementwas achieved with the SAS SST and the ZLES models in combination with the bounded central differential scheme. In addition, it was shownthat the ZLES model produced accurate results at all operating points, with discrepancy lower than 1%.
Keywords: aksialne turbine; napoved izkoristka; računalniška dinamika tekočin; turbulentni modeli; vodne turbine; ZLES